Incidencia en la criminalidad por la limitación del uso de armas de fuego dotadas por el estado a la policía nacional y por la falta de medios y armas adecuadas a los agentes de seguridad penitenciaria - Castillo Oviedo, Juletsy Jamileth (2022)
This research work is entitled: "Incidence in crime due to the limitation of the use of firearms provided by the State to the National Police and due to the lack of adequate means and weapons to the Penitentiary Security Agents" the objective of the development of This topic of legal research is to establish how the fear of police officers to use their firearms in the fulfillment of their legal duty affects the increase in crime, this situation will also be covered within the Centers of Social Rehabilitation, where prison security agents are in charge of internal security and who cannot counteract crime due to the lack of adequate means and weapons. Different research parameters established for the development of this topic of legal importance, such as doctrinal, legal, and conceptual. In the same way, the scientific, inductive, deductive, analytical, exegetical, hermeneutical, comparative, statistical, and synthetic methods were used, additionally the application of techniques such as the survey and interview, for which the city of Loja was taken as a sample to get criteria from professionals and specialists in the field to verify the problem and suggest a solution of incorporating a reform to our legislation in order to fight this problem that society suffers from, such as criminality. With this study, it is evident that, although there is indeed the provision of firearms to the national police, these servers are restricted from using them for fear of being awarded legal reprisals, on the other hand, the reality of our country regarding the increase in crime at the same time is reflected inside the penitentiary centers, in which there have been frequent armed confrontations between criminal gangs, situations in which prison security agents cannot intervene due to the lack of adequate means and weapons.